The Impact of Carbon Performance and Carbon Information Disclosure on Firm Value: Financial Performance as a Mediator in Indonesian Listed Companies - Lestari, Emi; Nugroho, Mulyanto; Pristiana, Ulfi (Journal of Ecohumanism, 2024)
This study aims to provide empirical evidence on whether carbon performance and carbon information disclosure influence firm value, with financial performance serving as a mediating variable in the Indonesian capital market. The research employs a quantitative approach, utilizing secondary data from companies listed on the Indonesia Stock Exchange (IDX). The sample was collected using purposive sampling, comprising 176 companies over the period of 2020–2022, and analyzed using Structural Equation Modeling (SEM) with the SmartPLS program. The results indicate that carbon performance has a significant positive effect on financial performance, measured by ROA and ROE, and on firm value, measured by PBV and Tobin’s Q. Carbon information disclosure also shows a significant positive impact on financial performance but an insignificant positive effect on firm value. Financial performance has a significant positive influence on firm value and mediates the positive impact of carbon performance on firm value; however, it does not mediate the relationship between carbon disclosure and firm value.